Glycopeptidolipid glycosylation controls surface properties and pathogenicity in Mycobacterium abscessus. Issue 5 (19th May 2022) - Daher, Wassim; Leclercq, Louis-David; Johansen, Matt D.; Hamela, Claire; Karam, Jona; Trivelli, Xavier; Nigou, Jérôme; Guérardel, Yann; Kremer, Laurent
Summary: Mycobacterium abscessus is an emerging and difficult-to-manage mycobacterial species that exhibits smooth (S) or rough (R) morphotypes. Disruption of glycopeptidolipid (GPL) production results in transition from S to R and severe lung disease. A structure-activity relationship study was undertaken to decipher the role of GPL glycosylation in morphotype transition and pathogenesis. Deletion of gtf3 uncovered the prominent role of the extra rhamnose in enhancing mannose receptor-mediated internalization of M. abscessus by macrophages. In contrast, the absence of the 6-deoxy-talose and the first rhamnose in mutants lacking gtf1 and gtf2, respectively, affected M abscessus phagocytosis but also resulted in the S-to-R transition. Strikingly, gtf1 and gtf2 mutants displayed a strong propensity to form cords and abscesses in zebrafish, leading to robust and lethal infection. Together, these results underscore the importance and differential contribution of GPL monosaccharides in promoting virulence and infection outcomes. Graphical abstract: Highlights: Gtf1, Gtf2, and Gtf3 transfer deoxy-talose, internal and terminal rhamnose on GPL Gtf3 is needed for efficient bacterial uptake by macrophages via mannose receptor Deletion of Gtf1 or Gtf2 leads to rough corded bacilli and increased virulence GPL glycosylation controls Mycobacterium abscessus surface properties and pathogenicity Abstract : Glycopeptidolipids (GPLs) are major surface-associated lipids characterizing smooth M. abscessus . In this study, Daher et al. establish the importance and contribution of the various monosaccharide-decorating GPLs in internalization of the bacilli by macrophages and in controlling pathogenicity in zebrafish embryos.